ANALYSIS OF BOTTOM MIXING ON THE PROCESSES OF LIME DISSOLVING, DEPHOSPHORIZATION AND DESULFURIZATION OF METAL IN ARC STEEL-MAKING FURNACE - V. F. Sobolev; N. V. Andrianov; S. V. Terletski; M. A. Murikov; A. A. Chichko (Литьë и металлургия, 2006)
It is established experimentally that increase of intensity  of metal blowout in arc steel furnace is accelerating the dissolving of lime in slag. The operative regime of blowout in the arc furnace BM Z practically does not exert considerable influence on sulfur content in metal. It is shown that fettling wear in a complicated way depends on intensity of metal blowout what is connected with its dependence on FeO and SiO2 content.